Modernization of Turkey under Kamal Ataturk - Daud, Ismail; Nooraihan, Ali; Fadzli, Adam (Canadian Center of Science and Education, 2015)
Mustafa Kamal Ataturk considered one of the important figures who shape the modern life of Turkish nations. Kamal’s ideology and his political structure are important to be studied since both gives important contributions towards the establishment of modern secular Turkey. This paper discusses Turkey under Kamal Atarturk. Using a secondary analysis, published materials written by scholars and writers in the field, some views and analysis of scholars like Bernard Lewis, Kemal H Karpat and several others, are reviewed and analyzed. It was found that Kemal’s revolutions and reforms has brought Turkey into a new era of modernization on certain aspects but from different angels, he failed to preserve Islamic traditions and culture when he consciously amended the constitution of his country only for achieving his personal will ‘Modern Turkey’. Amongst his reform were the establishment of Kamalist republic, the attack on traditional Islamic leadership, the implementation of modernist Turkified Islam and the attack on Islamic culture. These four aspects are discussed throughout this paper.